The Effects of Nanosilver on Bacterial Contamination and Increase Durability Cultivars of Rosa hybrida L. Through of Stenting Method: Nanosilver in Rosa Stenting Method - Shaafi, Bahareh; Kahrizi, Danial; Zebarjadi, Alireza; Azadi, Pejman (Cellular and Molecular Biology, 2022)
The rose flower (Rosa hybrida L.) is one of the world’s most popular flowers among ornamental plants and the cut rose flower industry is the most important aspect of the rose culture industry in the world. The stenting method (cutting and grafting) uses a stem containing a leaf and a dormant bud as a scion, which is grafted onto an internode from the rootless rootstock so that the formation of the graft and the induction of the root on the rootstock are carried out simultaneously. In this method, Natal Briar is often used due to its desirable traits such as high rooting, the possibility of faster regeneration after cutting, the ability to adapt to different culture media and high resistance to root diseases. Most imported Natal Briar rootstocks, in addition to increasing the cost of producing hybrid roses, have a percentage of Agrobacterium contamination that can reduce the efficiency of stenting. Therefore, using the tissue culture technique to propagate the base is one of the important solutions. But one of the problems of tissue culture is the control of bacterial contamination so that these factors grow faster than explants and absorbing carbohydrate sources from the culture medium prevents regeneration of Natal Briar rootstocks. Nanotechnology today has expanded the field of application of nanomaterials due to the increase in the surface-to-volume ratio, electron transfer ability and surface reaction capability. Inhibit DNA replication and destroy the cellular structure of Agrobacterium. Therefore, the use of appropriate concentrations of Nanosilver in the culture medium of Natal Briar rootstocks increases the economic efficiency and durability of Rosa hybrida cultivars obtained by the stenting method.